Clinical and epidemiological characteristics of hospitalizations for diabetic ketoacidosis in children and adolescentes - Bruno Kostrzevicz Campos de Oliveira; Ian Mateus da Silva; Deisi Maria Vargas (O Mundo da Saúde)
The aim of this study was to analyze the clinical and epidemiological characteristics of hospitalizations for diabetic ketoacidosis (DKA) in children and adolescents admitted to a reference service of the Brazilian Unified Health System (SUS). This was a cross-sectional study based on the analysis of secondary data extracted from medical records. The variables investigated included sex, age, nutritional status, season of the year, signs and symptoms at admission, predisposing factors, length of hospitalization, ICU admission, complications, degree of acidosis, first decompensation, and therapeutic protocols used. A higher frequency of hospitalizations was observed among adolescents (54.7%), females (57.1%), and during the winter (30.9%). The mean age was 10.1 years. The most prevalent signs and symptoms at admission were dehydration, vomiting, nausea, and abdominal pain. The main causes associated with DKA were infections and missed insulin doses (49.9%). Complications occurred in 50% of cases, with hypokalemia and hyponatremia being the most prominent. Most hospitalizations involved mild or moderate degrees of acidosis (85.8%). First decompensation cases occurred in younger children, usually presenting with classic diabetes symptoms (polydipsia, polyuria, polyphagia). Among patients with a previous diagnosis, nausea and vomiting were more common. The most frequently used treatment consisted of continuous infusion of regular insulin and hydration with 0.9% saline solution. Hospitalizations for DKA were more frequent among female adolescents, especially during the winter. Mild to moderate acidosis predominated, with treatment aligned with current guidelines.